The effectiveness of input and output in vocabulary acquisition among primary ESL learners / Mellisa Chin Lee Lee - Chin, Mellisa Lee Lee (2014)
The role of input and output in interaction has always been seen as an entirety in the language-learning domain. Driven by three distinctive frameworks, earlier works suggested that the Interaction Hypothesis facilitates the Input Hypothesis and the Output Hypothesis in language development. This experimental study was designed to investigate the effects of pre-modified input, negotiated interaction and output in L2 vocabulary comprehension and acquisition. A sample of 45 primary school ESL learners with similar L1 background was divided into three groups (GPIO–premodified input, GINW–negotiated input without output, GINP–negotiated input with output). Each group learned the target vocabulary items with pictures through different approaches based on the corresponding independent variables. Data from the pre-test and three post-tests were then subjected to t-tests and ANOVA. This study replicates the findings of de la Fuente (2002), which suggested that negotiated interaction benefited L2 vocabulary comprehension, and provides explanation for the apparent exceptions in the study. Analysis also reveals that a fusion of negotiated interaction and output production had positive effects on both receptive and productive acquisition. This information can be used to develop targeted interventions by incorporating interactive tasks aimed at young ESL learners in everyday classrooms for vocabulary acquisition.